Students’ Perception on the use of Quillbot as Paraphrasing Tool in Paragraph Writing - Wahyuningsih, Alfiani; Suhartono, Luwandi; Surmiyati, Surmiyati (Journal of English Language and Education, 2025)
This study looks into how students in the English Language Education Study Program at Universitas Tanjungpura perceive QuillBot as a paraphrasing tool when composing paragraphs. The goals were to investigate how students’ rate QuillBot in terms of utility, ease of use, supportive conditions, and social influence, as well as to find the most important aspect influencing their acceptance of the technology. The study took a descriptive quantitative method and was guided by Venkatesh's Unified Theory of Acceptance and Use of Technology (UTAUT). A trustworthy and validated online survey was used to gather data. The findings demonstrate that students' opinions of all UTAUT constructs were largely favourable. Students’ perceived QuillBot was simple to use, good at enhancing sentence structure and vocabulary, and useful for creating well-organized paragraphs. These findings imply that using AI-assisted writing tools such as QuillBot can aid academic writing development in English language instruction. Future research should compare QuillBot to other paraphrase platforms to determine its impact on long-term writing competency.